An analysis of stress over riveted repair on a stiffened panel / Ramyzan Ramly and Wahyu Kuntjoro - Ramly, Ramyzan; Kuntjoro, Wahyu (2005)
There are a few thousands old or aging commercial aircrafts operating today. It is expected that all old or aging aircrafts will experience damages whether little or large. Damages in aircraft structures are classified as negligible intolerable. Since commercial aircrafts are constructed to be in damage tolerant design (DTD), negligible damage is not threatening and the aircraft can still operate under some limitations.